2015
DOI: 10.1108/jcm-09-2014-1146
|View full text |Cite
|
Sign up to set email alerts
|

Family meals and identity in urban China

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:123705 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 82 publications
1
33
0
2
Order By: Relevance
“…A previous study in Belgium showed that working households were less likely to spend time on cooking than non-working households (Daniels & Glorieux, 2015), a finding which is likely to reflect the situation in China. Owing to China's rapid socioeconomic development, people's eating patterns have been fundamentally changed (Yu, Veeck, & Yu, 2015). In many Chinese cities, especially a metropolis such as Shanghai, people have become accustomed to working or studying for many hours a day (Han, 2018).…”
Section: Current Remedies To Help Improve Their Immune Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Belgium showed that working households were less likely to spend time on cooking than non-working households (Daniels & Glorieux, 2015), a finding which is likely to reflect the situation in China. Owing to China's rapid socioeconomic development, people's eating patterns have been fundamentally changed (Yu, Veeck, & Yu, 2015). In many Chinese cities, especially a metropolis such as Shanghai, people have become accustomed to working or studying for many hours a day (Han, 2018).…”
Section: Current Remedies To Help Improve Their Immune Healthmentioning
confidence: 99%
“…In many Chinese cities, especially a metropolis such as Shanghai, people have become accustomed to working or studying for many hours a day (Han, 2018). Busier schedules for adults and school children means that family members are more likely to reduce the time they spend cooking and choose less time-consuming food options (Veeck, Yu, Yu, Veeck, & Gentry, 2014), such as patronizing fast food restaurants, choosing processed food products or eating snacks (Yu et al, 2015).…”
Section: Current Remedies To Help Improve Their Immune Healthmentioning
confidence: 99%
“…Chinese collectivistic culture highly values family relationships that are characterized by harmony, togetherness, intimacy, cohesiveness, and reciprocity of responsibilities (Bond, 1996; Shek, 2001). Taking meals together serves to reaffirm family relationships and construct the collective family identity (Lai-Yeung, 2015; Wong, 2010; Yu, Veeck, & Yu, 2015). We conducted a series of community-based family intervention studies under The FAMILY Project, including Happy Family Kitchen (HFK I) and Happy Family Kitchen II (HFK II), which applied a positive psychology framework to a family cooking and dining setting to improve family communication and well-being in Hong Kong (Ho et al, 2016a, 2016b, 2016c, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aktivitas makan bersama keluarga digambarkan sebagai suatu aktivitas di mana seluruh anggota keluarga berkumpul dan duduk bersama di meja makan untuk makan bersama, di mana hal itu terutama ditandai oleh adanya percakapan yang intim selama aktivitas tersebut berlangsung (Cinotto, 2006). Waktu makan dikatakan menjadi kesempatan bagi anggota keluarga untuk bersama di tengah kesibukan sepanjang hari masing-masing anggota keluarga (Hamilton & Wilson, 2009) yang memberikan individu perasaan sebagai satu keluarga (family identity) (Evans & Rodger, 2008;Yu, Veeck, & Yu, 2015). Kebersamaan dan percakapan intim yang terjadi selama waktu makan dapat memberikan efek rekreasional bagi anggota keluarga, berupa perasaan senang, bahagia, dan positif (Evans & Rodger, 2008).…”
Section: Diskusiunclassified